Experimental study of PV/T air solar collector and generation of fuzzy membership functions - Othman, M. (Springer Singapore, 2020)
This paper discussed the experimental study on the performance of a PV/T air solar collector. The operation of the solar collector is observed and studied under the change of parameters which are temperature, solar irradiance and air mass flow rate. The data collected is then used in the generation of fuzzy membership functions of the solar collector by using inductive reasoning. The generation scheme is based on minimum entropy method. The membership functions of each parameter are also tabulated and shown in graphs. Â© The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2020.